ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JAMINAN KEAMANAN DALAM TRANSAKSI DENGAN MENGGUNAKAN SISTEM E-COMMERCE PADA BAJIKI STORE MAKASSAR - Mariah Mariah; Rahmat Kurniady (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this study is to determine what factors affect the security of transactions using the E-commerce system at Bajiki Store Makassar. The location of the study was conducted at Bajiki Store Makassar where the population in this study is all Bajiki Store Makassar consumers who have purchased their products or services based on data obtained from Bajiki Store Makassar through E-commerce system. Based on the results of the analysis of the data collected, it can be concluded: From the results of data processing using SPSS, it can be concluded that Firewall, NFC, and PIN affect transaction security guarantee